Production, markets, regulation and technology in organic agriculture - Marsden, Terry (2020)
This study deals with organic agriculture in Europe and looks at recent trends and implications for research and development. The work pays attention to various aspects related to organic agriculture, especially at the European level. Production aspects are reviewed; the emergence and regulation of new markets and compares the regulations in force in various countries. It also highlights the differences and specifications that, both at the level of the ID and in the role of the public and private sectors, organic production presents with respect to traditional agriculture. The paper ends with an analysis of the trends in the expansion of organic products and their penetration in the markets in relation to conventional agri-food chains, highlighting the role of the public sector.